The effect of different periods of early fasting on the economic and productive traits of broiler at Al-Muthanna Governorate - Blaw, Hayder H.; Abed, Miqdad J.; Al-Zamili, Ibrahim F. B; Gharawi, Jassim K. Al (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed the effect of different periods of early fasting on productive and economic traits of broiler. A total of 180 chicks of the ROSS 308 were used, one day, 43 g average weight, were randomly distributed into three treatments, as follows; the first treatment (T1) free feeding from one day until the end of the experiment (6 weeks) as a control treatment, the second treatment (T2) was lifted feed two days apart per week during the period of food rationing starting from 7-21 days, and the third treatment (T3) was provided feed between one and the other reciprocally during the same time rationing period, after the end of the fasting period in the second and third treatment at the age of 21 days, it was provided for brood rearing until the 6-week marketing date. The results of the experiment indicated a compensatory growth for the birds in the two treatments of time rationing, as the weight rates of the living body in the fasting treatments (T2 and T3) compared with the control treatment at the age of 6 weeks, the results showed that early fasting treatments were significantly (P≤0.05) improved in the productive and economic traits studied compared with the control treatment. The results showed the superiority of T2 on weight gain, reflected on the increase in revenue generated, as well as a decrease in feed consumption in T3, which was reflected in the feed costs, as a result showed in T3 exceeded the amount of profit per chicken, 0.16 compared to the control treatment.